Language Style Analysis in “Downton Abbey: New Era” Movie - Prihatin Puji Astuti; Ria Antika; Adissa Putri (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
Language style is a way of people talking and expressing messages, thoughts, or ideas to others. Everyone will use a different style of language when speaking. This happens for various reasons, including: the interlocutor factor, the purpose of the conversation, the context of the conversation, the time and place where the conversation was carried out, and so on. This study aims to analyze the types of language style and the factors of the use of language style spoken by the actors in the film "Downton Abbey: New Era”. In this study, the writers used the theory proposed by Joos (1967) in his book The Five Clocks about types of language style and Holmes (1992) about the factors that influence them. The theory about the style of language that are explored in the utterances spoken by the actors in the film are frozen style, formal style, consultative style, casual style, and intimate style. While the factors that appear are setting, participant, topic, and function. This study applied a qualitative method with literature study as the approach.